Register of newly diagnosed diabetic children. Issue 5983 (6th September 1975) - Bloom, A; Hayes, T M; Gamble, D R
Abstract : In November 1972 the British Diabetic Association sponsored a register to which notification was invited of all new cases of diabetes occurring in children aged 0-15 years in Great Britain and Ireland. More than 2000 cases were notified in the first two years. Notification suggested that there was a minimum yearly incidence of 7-67 cases per 100 000, though incidences varied from year to year and by geographical area. Several reports of simultaneous onset of diabetes in sibs of different ages provided evidence of clustering. A seasonal variation in incidence was found in children aged 5-15 years with peaks in the autumn and winter. The age distribution was bimodal with a main peak at about 11 years and a secondary peak at about 5 years. The sex ratio showed a male excess from 0-4 years and from 11-15 years and a female excess from 5-10 years. Overall there were slightly more male cases. Altogether 11% of patients had a first-degree relative with diabetes. The register and several investigations based on it will continue.